Evaluating the Impact of Macroeconomic Policy Interventions and Recession on a Sewage Treatment PPP Project Using a System Dynamic Model - Qian Liu; Zaiyi Liao; Qi Guo; Dagmawi Mulugeta Degefu; Liang Yuan; Shenjun Jiang; Feihong Jian (Advances in Civil Engineering)
The revenue of a public-private partnership (PPP) project is influenced by macroeconomic scenarios such as economic recession and policy adjustments. But these macrofactors and their dynamic relations with microfactors in PPP projects have not been thoroughly understood. In this article, system dynamics (SD) and real option (RO) are integrated to develop a novel model to investigate the impacts of the macro-risk factors on the revenue of PPP projects. Five scenarios were studied through simulation. The results indicate that the loan interest rate and tax rate are negatively correlated to the revenue, while the GDP growth rate and self-owned capital rate are positively correlated. This indicates that the government can stimulate the private sector to invest in PPP projects by providing lower loan interest and increasing the self-owned capital rate. This integrated approach has been proposed for use by decision-makers to evaluate the impact of economics and policies in the future. This study provides a comprehensive review and reliable theoretical analysis regarding the adoption of PPP by China’s local governments, yielding to main policy implications for further promoting the efficiency of PPP development.